Gerenciamento de resíduos hospitalares: uma proposta de conscientização para o descarte correto de resíduos de serviços de saúde no Hospital Universitário de Santa Maria - RS - Soares, Daniela Beatriz Souza (2024)
Hospitals generate an increasing volume of waste, which may be infectious, toxic, or radioactive. The correct steps in disposing of waste from healthcare services aim to reduce work accidents during their handling, thus leading to a greater perception of their importance. So that there is environmental balance in health institutions. Therefore, for the incorrect disposal of waste from healthcare services to be mitigated, there must be planning and training of healthcare professionals, focusing on the correct segregation of this waste and promoting the protection of public and environmental health. The Hospital Universitário de Santa Maria is considered a reference institution for the central region of Rio Grande do Sul. It is worth noting that with the intensity of procedures that are carried out daily, the production of waste from healthcare services becomes yet another concern. Given this context, the main objective of the study in question is to propose as an improvement the construction of a technological product in the form of a booklet to train employees who perform professional activities at HUSM. Through documentary research, it was possible to carry out a situational diagnosis to determine whether the Health Service Waste Management Plan complies with current requirements and standards and whether the process of disposing of health service waste occurs correctly. The investigation took place through the application of a questionnaire offered to HUSM nursing professionals. The research carried out was qualitative and descriptive and the data analysis method was carried out using descriptive statistics and t-test. The results showed that professionals, in general, have good knowledge about the topic investigated, however, they indicated that the need for training on the subject of health service waste needs to be carried out more frequently for all groups investigated. It was also clear that not all professionals were aware of the existence of the PGRSS at HUSM, nor did they practice good practices for the correct disposal of healthcare waste with the frequency that they should occur. Elements such as gender, age, length of service, work shift, and work regime also influence the behavior of the professionals surveyed, pointing out that those with less time working at the institution, governed by the EBSERH regime, received more training on the disposal of waste from healthcare services. Healthier than professionals with longer service hired through the RJU labor regime. Furthermore, with the construction of the booklet, the main objective of this research, it will be possible to cover all professionals to provide greater knowledge regarding the HUSM Health Service Waste Management Plan and good practices on waste disposal from health services. This research may be used to contribute to decision-making and actions that promote improvements in the service provided about the disposal of health service waste.